On the Demand for High-Beta Stocks: Evidence from Mutual Funds - Christoffersen, Susan E. K.; Simutin, Mikhail (Review of Financial Studies, 2017)
Prior studies have documented that pension plan sponsors often monitor a fund's performance relative to a benchmark. We use a first-difference approach to show that in an effort to beat benchmarks, fund managers controlling large pension assets tend to increase their exposure to high-beta stocks, while aiming to maintain tracking errors around the benchmark. The findings support theoretical conjectures that benchmarking can lead managers to tilt their portfolio toward high-beta stocks and away from low-beta stocks, which can reinforce observed pricing anomalies.